1969
DOI: 10.1530/acta.0.0610687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Starvation on Levels of Corticotrophin Releasing Factor, Corticotrophin and Plasma Corticosterone in Rats

Abstract: Rats were starved for seven days and the effects on corticotrophin releasing factor (CRF) content in the stalk median eminence (SME), corticotrophin content in the anterior pituitary gland (AP), basal plasma corticosterone response to ethyl ether stress were determined. The weight changes in the adrenal and anterior pituitary glands were also studied. When compared to the control group, starvation resulted in a significant increase in stored GRF in the SME. There was a decrease in the corticotrophin content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…Chowers et al [2] also re ported a remarkable increase in corticosterone levels in plasma after 7 days of food depriva tion. In our study, an increment in blood corticosterone levels by food deprivation was not observed.…”
Section: Change In the Daily Patterns O F Locomotor Activitymentioning
confidence: 86%
“…Chowers et al [2] also re ported a remarkable increase in corticosterone levels in plasma after 7 days of food depriva tion. In our study, an increment in blood corticosterone levels by food deprivation was not observed.…”
Section: Change In the Daily Patterns O F Locomotor Activitymentioning
confidence: 86%
“…Acetyl promazine,thiopentone and halothanedid not themselves elicit an increase. The adrenocortical response to anaesthesia depends upon the nature of the anaesthetic ; many authors have shown that ether anaesthesia produces a response in man and other animals (Virtue, Helmreich & Gainza, 1957;Chowers, Einat & Feldman, 1969;Oyama, Shibata, Matsuki & Kudo, 1969) as does Nembutal (Moncloa, Péron & Dorfman, 1959;Nagle, Cammock, Nyhus & Harkins, 1965), whereas thiopentone and halothane produce no change in man (Oyama, Shibata, Matusmoto, Takiguchi & Kudo, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The HPA axis controls circulating levels of GCs, which are the main endocrine signal in the adaptation to stress and are also a major signal for the maintenance of energy homeostasis via control of metabolism and appetite (Castonguay, 1991;Sapolsky et al, 2000). Fasting is a metabolic stress that increases the circulating levels of GCs and decreases the circulating levels of leptin (Chowers et al, 1969;Ahima, 2000), the primary endocrine signal of the nutritional state. This hormonal profile sets the stage for vital behavioral and physiological adaptations that take place during caloric deficit to promote the reestablishment of energy balance.…”
Section: Introductionmentioning
confidence: 99%